Adoption Of Selected Wheat Production Technologies In Two Northern Districts Of Bangladesh - Rahman, MS; Haque, Zerina (International Journal of Agricultural Research, Innovation and Technology, 2013)
The study was conducted in two major wheat growing areas of Bangladesh to determine the adoption level and factors affecting the adoption of wheat production practices in the study areas during 2011. Descriptive statistics along with multiple regression technique was used to achieve the objectives. The results revealed that most of the farmers (60.91%) in the study areas were cultivating Shatabdi variety of wheat. Adoption level of seed rate, TSP and MoP application were found to be very low. On the other hand, production practices like time of wheat sowing and number of irrigation were highly adopted by the farmers. Most of the farmers (69.09%) applied TSP below the recommended dose while 81.82% of the farmers applied MoP over the recommended dose. The study also revealed a positive and significant relationship between adoption and the variables like education, experience and extension contact. Lack of proper information and technical knowledge were the major problems that hinder the adoption of wheat production technologies in the study areas. Adoption gaps are needed to be eliminated to enhance the productivity as well as net return of wheat cultivation. Int. J. Agril. Res. Innov. & Tech. 3 (1): 5-11, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16043